PERKEMBANGAN ARTIFICIAL INTELLIGENCE (AI) PENERAPAN CYBER LAW DI INDONESIA - Cita, Ni Putu Wulan Cintana; Cokorde Istri Dian Laksmi Dewi; Kadek Ary Purnama Dewi (VYAVAHARA DUTA, 2026)
The development of information and communication technology has significantly impacted various aspects of human life, including the emergence of new challenges in the form of cybercrime. The internet, as a global computer network, has become a medium that facilitates interaction and information access, but also creates opportunities for criminal acts in the virtual world. One of the responses to these threats is the utilization of Artificial Intelligence (AI) in cybersecurity and the enforcement of digital law (Cyber law). AI has the capability to detect, analyze, and respond to cyberattacks quickly and efficiently. This paper aims to explore the development and history of AI as well as its application in cyber law enforcement in Indonesia. In addition to providing insights into the dynamics of digital crime, this study is expected to enhance knowledge in the field of criminology, particularly regarding the role of technology in modern law enforcement. This discussion is crucial in strengthening national digital resilience and addressing the increasingly complex challenges of globalization.